Altered fecal microbiota composition in all male aggressor‐exposed rodent model simulating features of post‐traumatic stress disorder - Gautam, Aarti; Kumar, Raina; Chakraborty, Nabarun; Muhie, Seid; Hoke, Allison; Hammamieh, Rasha; Jett, Marti (Journal of neuroscience research, 2018)
The bidirectional role of gut–brain axis that integrates the gut and central nervous system activities has recently been investigated. We studied “cage‐within‐cage resident‐intruder” all‐male model, where subject male mice (C57BL/6J) are exposed to aggressor mice (SJL albino), and gut microbiota‐derived metabolites were identified in plasma after 10 days of exposure. We assessed 16S ribosomal RNA gene from fecal samples collected daily from these mice during the 10‐day study. Alpha diversity using Chao indices indicated no change in diversity in aggressor‐exposed samples. The abundance profile showed the top phyla were Firmicutes and Bacteroidetes, Tenericutes, Verrucomicrobia, Actinobacteria and Proteobacteria, respectively. The phyla Firmicutes and Bacteroidetes are vulnerable to PTSD‐eliciting stress and the Firmicutes/Bacteroidetes ratio increases with stress. Principal coordinate analysis showed the control and aggressor‐exposed samples cluster separately where samples from early time points (day 1‐3) clustered together and were distinct from late time points (day 4‐9). The genus‐based analysis revealed all control time points clustered together and aggressor‐exposed samples had multiple clusters. The decrease in proportion of Firmicutes after aggressor exposure persisted throughout the study. The proportion of Verrucomicrobia immediately decreased and was significantly shifted at most of the later time points. The genus Oscillospira, Lactobacillus, Akkermansia and Anaeroplasma are the top four genera that differed between control and stressor‐exposed mice. The data showed immediate effect on microbiome composition during a 10 day time period of stress exposure. Studying the longitudinal effects of a stressor is an important step toward an improved mechanistic understanding of the microbiome dynamics.